Internship Implementation at PT Xtend Integrasi Indonesia - Yulita Halim (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Internship is a vocational programme designed to provide students with authentic workplace experience and to bridge the gap between school learning and industry practices. This paper reports the internship activities conducted at PT Xtend Integrasi Indonesia from June to December 2025. The internship involved project planning, system installation, software configuration, integration of IT-based solutions, and maintenance tasks such as fibre optic cable splicing and panel repair. Through these activities, students applied theoretical knowledge in practical contexts, thereby enhancing technical competencies in troubleshooting, hardware installation, and system integration. Beyond technical skills, the internship fostered soft skills including discipline, adaptability, teamwork, and communication, which are essential for professional success. Challenges such as technological gaps between school and industry, limited mentorship due to supervisors’ workload, and cultural adjustment to workplace discipline were encountered. These challenges were overcome through proactive learning, collaboration with colleagues, and flexibility in adapting to new environments. Overall, the internship programme significantly enhanced students’ readiness for professional work, strengthened their technical expertise, and contributed to the formation of professional identities.